Effects of strength training program and infrared thermography in soccer athletes injuries - Menezes, P.; Rhea, M. R.; Herdy, C.; Simao, R. (Sports, 2018)
The purpose of this investigation was to examine the effects of a periodized strength training program and the use of infrared thermography (IRT) in injuries mapping in under 20-year-old (U-20) soccer players. In this study, 26 professional soccer players participated in strength training (ST) twice a week and were tested with IRT consistently across the 1-year. Strength, vertical jump, heat differences and injuries were tracked and analyzed. Results: 69 injuries occurred during 12 months of tracking; most identified injuries were: contusions, sprains, strains to the thigh (n = 16), ankle (n = 15) and knee (n = 12). Differences (>7 °C) in IRT patterns were noted among injured and non-injured athletes. Significant improvements in strength (p < 0.005) were found for vertical jump, bench press, front lat pull down, shoulder press, leg press, leg curl and squat. Number of injuries decreased from 23 (33.3%) to 14 (20.3%) when early year rates were compared to late year (p < 0.005). Combined ST and IRT represent useful strategies for reducing injuries among U-20 soccer players.